The assessment of the rain erosivity in the Aures Massif (eastern Algeria) - Khentouche, Adel; Bella, Nassim (Acta Geographica Lodziensia, 2023)
In eastern Algeria and particularly on the Aures Massif, the phenomenon of erosion takes several forms and manifests itself spectacularly, especially on vulnerable and less-vegetated soils. Some soil scientists link soil genesis with the erosivity of rainfalls. This work aims at a spatio-temporal representation of rainfall erosivity according to a geostatistical approach that begins with the estimation of certain erosivity indices and ends with a precise zoning. The study showed that the physical characteristics of this space are varied, but the mountainous areas are most sensitive, with erosivity index values ranging from 20 to 50, and some stations on the piedmonts record average values. By contrast, the desert zones offer low values of below 5 according to the index of Arnoldus. The stations exposed to the north have markedly the highest erosivity values. In addition, rainfall erosivity increased according to altitude, and the correlation between rainfall and rainfall erosivity was very significant. Zoning of erosivity will provide decision-makers and technicians with a tool for management and decision-making to protect and ensure soil sustainability.